2006
DOI: 10.5194/cpd-2-1293-2006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coupled simulations of the mid-Holocene and Last Glacial Maximum: new results from PMIP2

Abstract: Abstract. A set of coupled ocean-atmosphere simulations using state of the art climate models is now available for the Last Glacial Maximum and the mid-Holocene through the second phase of the Paleoclimate Modeling Intercomparison Project (PMIP2). This study presents the large scale features of the simulated climates and compares the new model results to those of the atmospheric models from the first phase of the PMIP, for which sea surface temperature was prescribed or computed using simple slab ocean formula… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 48 publications
(48 reference statements)
2
20
0
Order By: Relevance
“…This is reflected by a higher dust deposition and a greater mobility of sand dunes (Rea 1994;Bigelow et al 1990;Adams 2003;Harrison et al 2001;Sarnthein 1978). In addition to the large DP, the global mean precipitation rate was lower during the LGM (e.g., Braconnot et al 2006). These are ideal conditions for dune activity.…”
Section: Discussionmentioning
confidence: 96%
“…This is reflected by a higher dust deposition and a greater mobility of sand dunes (Rea 1994;Bigelow et al 1990;Adams 2003;Harrison et al 2001;Sarnthein 1978). In addition to the large DP, the global mean precipitation rate was lower during the LGM (e.g., Braconnot et al 2006). These are ideal conditions for dune activity.…”
Section: Discussionmentioning
confidence: 96%
“…Coupled modeling studies of the LGM previously have shown widely varying changes to the LGM Atlantic meridional overturning circulation, but the interpretation of these differences has been difficult due to various forcings and boundary conditions used [ Hewitt et al , 2003; Kim , 2004; Kitoh et al , 2001; Peltier and Solheim , 2004; Shin et al , 2003b; Weber et al , 2007]. The second phase of the Paleoclimate Modeling Intercomparison Project (PMIP2) adopts standard forcings and boundary conditions to allow model‐model and model‐data comparisons for the LGM [ Braconnot et al , 2006].…”
Section: Modelsmentioning
confidence: 99%
“…In addition to using reconstructions for the validation of palaeoclimate model outputs (e.g. Braconnot et al 2007aBraconnot et al , 2007bRenssen et al 2009), the integration of modelling can provide improvements for quantitative climate reconstructions under environmental conditions that are strongly nonanaloguous with the present. An example of such a situation is the climate reconstructions from the last glacial period when the atmospheric CO 2 content was 180 ppm, thus nearly 50% lower than at present.…”
Section: Challenges and Future Developmentsmentioning
confidence: 99%
“…This need is, in part, a response to demands for quantitative reconstructions of past climates as input to, or more commonly, for validation of hindcasts by general circulation or Earth system models of past climate or land-cover patterns (e.g. Braconnot et al 2007aBraconnot et al , 2007bRenssen et al 2009;Schmidt 2010), in mapping past climate patterns in time and space (e.g. Heiri et al 2004;Morrill & Jacobsen 2005), in predicting the risk of future climate shifts (e.g.…”
Section: Introductionmentioning
confidence: 99%